2020
DOI: 10.3221/igf-esis.52.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concrete cover thickness and main reinforcement ratio on flexural behavior of RC beams strengthened by NSM-GFRP bars

Abstract: Experimental and numerical programs were conducted to investigate the effect of concrete cover and area of main steel reinforcement on the flexural behavior of strengthened RC beams by near-surface mounted glass fiber reinforced polymeric (NSM GFRP) bars of different lengths. Nine beams divided into three main groups were tested under four-point bending. The three beams of the first group were strengthened by different lengths of GFRP bars and having a concrete cover of 50 mm, while the three beams in the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The ductility index of the BN beam (ultimate deflection/first cracking deflection) is about 7.08. The behaviors of the solid (control) beam in the present work are similar to the behavior of beams found in [16][17][18].…”
Section: Solid (Control) Beamsupporting
confidence: 78%
“…The ductility index of the BN beam (ultimate deflection/first cracking deflection) is about 7.08. The behaviors of the solid (control) beam in the present work are similar to the behavior of beams found in [16][17][18].…”
Section: Solid (Control) Beamsupporting
confidence: 78%
“…Element SOLID 185 is used for the simulation of loading and bearing plates. This element is characterized by eight nodes with three translations nodal degrees of freedom in the nodal cartesian directions x, y, and z [7,[24][25][26][27][28]]. An experimentally tested beam-column joint was used from literature to validate numerical analysis via ANSYS software [29].…”
Section: T Numerical Analysis and Verification Modelmentioning
confidence: 99%
“…In the last decade, substantial efforts were made to extend FRP composite materials to the construction sector, and, finally, structural uses of composite materials have started to arise in civil structures. FRP composite materials are being used as interior and exterior reinforcements in the field of structural engineering due to the high tensile strength to weight ratio, higher stiffness, lower density, chemical attack resistance, and other properties [3][4][5][6][7][8]. Significant research activities in recent years have demonstrated that FRP materials can be used successfully to strengthen reinforced concrete structures [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, durability is much more than just material science. In this study we introduce a holistic approach that also includes the application or exposure to the operating environment [13]. For a truly durable solution the structural design plays a critical role in determining potential for cracking, which impacts the reinforcing requirements, crack spacing, and width.…”
Section: Introductionmentioning
confidence: 99%